Population cancer risks associated with coal mining: a systematic review. - Wiley D Jenkins; W Jay Christian; Georgia Mueller; K Thomas Robbins (PLoS ONE)
Background Coal is produced across 25 states and provides 42% of US energy. With production expected to increase 7.6% by 2035, proximate populations remain at risk of exposure to carcinogenic coal products such as silica dust and organic compounds. It is unclear if population exposure is associated with increased risk, or even which cancers have been studied in this regard. Methods We performed a systematic review of English-language manuscripts published since 1980 to determine if coal mining exposure was associated with increased cancer risk (incidence and mortality). Results Of 34 studies identified, 27 studied coal mining as an occupational exposure (coal miner cohort or as a retrospective risk factor) but only seven explored health effects in surrounding populations. Overall, risk assessments were reported for 20 cancer site categories, but their results and frequency varied considerably. Incidence and mortality risk assessments were: negative (no increase) for 12 sites; positive for 1 site; and discordant for 7 sites (e.g. lung, gastric). However, 10 sites had only a single study reporting incidence risk (4 sites had none), and 11 sites had only a single study reporting mortality risk (2 sites had none). The ecological study data were particularly meager, reporting assessments for only 9 sites. While mortality assessments were reported for each, 6 had only a single report and only 2 sites had reported incidence assessments. Conclusions The reported assessments are too meager, and at times contradictory, to make definitive conclusions about population cancer risk due to coal mining. However, the preponderance of this and other data support many of Hill's criteria for causation. The paucity of data regarding population exposure and risk, the widespread geographical extent of coal mining activity, and the continuing importance of coal for US energy, warrant further studies of population exposure and risk.